The Influence of Self Esteem on Smartphone Addiction with Academic Stress as Mediator Variables in Class XI Students Using Smartphones at SMA Negeri 12 Jakarta - Windicha Fitri, Rachmi; Arya Haninditya, Adam; Arini Ridwan, Vira (Lafadz Jaya Publisher, 2024)
This research is a quantitative study which aims to examine the influence of Self Esteem on Smartphone Addiction, the influence of Self Esteem on Academic Stress, the influence of Academic Stress on Smartphone Addiction, and the influence of Self Esteem and Academic Stress on Smartphone Addiction. The subjects in this research were class XI students at SMA Negeri 12 Jakarta, totaling 140 samples using the Simple Random Sampling technique. This research uses 3 measuring instrument scales, namely: the Self Esteem variable measuring instrument scale, the Academic Stress variable measuring instrument scale and the Smartphone Addiction variable measuring instrument scale. The results of this study show that, 1) There is a significant influence between Self Esteem on Smartphone Addiction with r = -0.26 and t = -3.30 (t > 1.96), 2) There is a significant influence between Self Esteem on Academic Stress with r = - 0.33 and t = - 4.12 (t > 1.96), 3) There is a significant influence between Academic Stress on Smartphone Addiction with r = 0.29 and t = 3.66 (t > 1.96) 4) Academic Stress functions as a Mediator on the Influence of Self Esteem on Smartphone Addiction with r = -0.105 and t = -2.375 (t >1.96).